The International Classification of Functioning, Disability and Health (ICF) in neurorehabilitation in Austria. Comparison of the healthprofessions occupational therapy, speech-and language therapy and physiotherapy / Die Internationale Klassifikation der Funktionsfähigkeit, Behinderung und Gesundheit in der Neurorehabilitation in Österreich. Vergleich der Berufsgruppen Ergotherapie, Logopädie und Physiotherapie - Aftenberger Hannes; Schwarze Gabriele; Salchinger Beate; Rother Angelika (Sciendo, 2017)
The International Classification of Functioning Disability and Health (ICF) provides the language and a framework applying a unified and standardized form to describe health and conditions related to health. Teams who work in an interdisciplinary and multi professional way, as it is the case in neuro rehabilitation, can profit from integrating the ICF. The aim of this paper was to show how well implemented the ICF is in Austria with occupational therapists, speech and language therapists and physiotherapists working in neuro rehabilitation.